PROFITABILITY, RISK, AND COMPANY SIZE: UNVEILING THEIR ROLE IN ESG DISCLOSURE - Elysia Stephanie; Yanti Yanti (Graduate Program of Universitas Tarumanagara, 2026)
This study aims to analyze the factors that influence Environmental, Social, and Governance (ESG) Disclosure. Awareness of ESG has been increasing, as evidenced by the growing number of companies that disclose sustainability information in their corporate reports. ESG disclosure serves as a tool for companies to meet stakeholder demands by promoting transparency and accountability. The independent variables used in this study are profitability, risk, and company size, with ESG disclosure as the dependent variable. The study employs a quantitative descriptive approach and the purposive sampling technique. The population that meets the sampling criteria consists of 38 companies out of 131 companies, focusing on the consumer non-cyclicals sector listed on the Indonesian Stock Exchange (IDX) during the period 2022 to 2024. The data used is secondary data obtained from financial reports and sustainability reports, which are accessible through the official IDX website and the companies’ official websites. The collected data were analyzed using EViews version 12. The results of this study indicate that company size has a positive and significant effect on ESG disclosure. This finding supports legitimacy theory, suggesting that larger companies tend to increase their ESG disclosure to gain recognition from stakeholders. On the other hand, profitability and risk have a positive but insignificant effect on ESG disclosure.